„Nulla calamitas sola. One difficulty is calling another!“ Municipal administration of Slaný during the Thirty Years´ War (Theatrum historiae, 2015)
During the Thirty Years’ War the municipal administration of town Slaný was, like in other towns, mainly influenced by the military events. However, there was one another significant factor that influenced the form of town administration. In 1623 the heavily indebted town was pawned and fifteen years later was sold to Jaroslav Bořita of Martinitz. The royal town Slaný became a manorial town with all the consequences arising of that. In many cases it is very difficult to say which of these factors were crucial therefore this article focuses also on the new elements in the municipal administration related to a change in its legal status, respectively new lords’ intervention in municipal administration.
Keywords: Slaný; the Thirty Years´ War; municipal administration; Jaroslav Bořita of Martinitz; the early modern age